Developing an investment preference model for family takaful investment link plan in Klang Valley, Malaysia - Parveen, Tamiza (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
Family Takaful is a Shari'ah compliant insurance alternative that offers investment options to Takaful participants. Family Takaful investment-linked products provide a means of investment with proper financial protection. However, based on market observation, the penetration rate of Family Takaful remains small compared to that of conventional life insurance. According to the Malaysian Takaful Dynamic, the current penetration rate for Family Takaful was 14.5 per cent, while that of conventional life insurance was 41.2 per cent. Lack of awareness among the investors has limited the potential for unit-linked products with an emphasis on the investment link products in the Takaful industry. This research focuses on the investment aspect of Family Takaful known as investment-link Takaful by developing an investment preference model. Theory of Planned Behaviour (TPB) and Theory of Interpersonal Behaviour (TIB) are used to develop the conceptual framework. This study uses a quantitative research method. A questionnaire survey is used to collect primary data from 323 Family Takaful plan holders. Structural Equation Modelling (SEM) results validate the conceptual model. The findings reveal that perceived risk has a negative impact on attitudes toward the investment-linked plan and awareness has a positive impact. Attitude has a positive impact on preference towards Family Takaful investment- linked plan. Attitude is also found to play a mediating role between religiosity, awareness and preference. The results provided by the study contribute to the existing literature and benefit Takaful operators in understanding the significant factors that affect investor preference in investment-link Family Takaful plans. Keywords: Takaful, Investment-linked plan, Malaysia, Shari'ah